Improving the utilization of distilled dried grains with soluble by enzymes and yeast supplementations for production and economic sustainability and digestibility of laying - Attia, Youssef; A. Ahmed, Ali Kh. (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2023)
A study was conducted to test the influence of different concentrations of distillers dried grains with soluble (DDGS) with or without a commercial enzyme preparation (Kemzyme plus dry®) at 0 and 500 g/ ton feed and Saccharomyces cerevisiae at 1 kg/ton feed in native Inshas laying hens’ diets to evaluate the effects on production and economic sustainability, nutrients digestibility, nitrogen, and phosphorus retention. A total number of 270 Inshas laying hens, local 28-week-old were randomly divided into nine experimental groups, each group containing three replicates of 10 hens. The experimental treatments include three levels (0, 10, and 20%) of DDGS without or with two additives supplementation. The study revealed that body weight and the productive performance of laying hens were not significantly affected by dietary treatments. Feed intake decreased progressively with increasing DDGS levels; however, enzyme and yeast supplementation completely recovered the adverse influence of DDGS. Both nitrogen and P retention increased with increasing DDGS, in contrast, N and P excretion decreased as DDGS increased, but enzymes or yeast had no effects within each DDGS level. Moreover, there was a significant increase in the relative economic efficiency due to feeding laying hens with diet containing 10% DDGS compared to the control. It was concluded that corn DDGS could be provided to laying hens up to 20% without adverse effects on productive and economic efficiency while adding enzymes or Saccharomyces cerevisiae decreased N and P excretion, suggesting positive environmental impacts.